Virtual SDN embedding with differentiated QoS under multiple controller - Zhi-yuan ZHAO; Xiang-ru MENG; Yu-ze SU; Zhen-tao LI (Tongxin xuebao)
In SDN virtua1ization environment under mu1tip1e contro11ers，with the goa1 of minimum the mean de1ay between contro1 paths，the 1oad imba1ance of contro11ers，and the cost of embedding，mathematica1 mode1s of the contro11er p1acement and the virtua1 SDN embedding prob1em were bui1t，and a virtua1 SDN embedding method with differentiated QoS under mu1tip1e contro11ers was proposed.The simu1ation resu1ts show that the proposed a1gorithm can satisfy various virtua1 networks QoS for users，keep 1oad ba1ance between contro11ers and increase the acceptance ratio and the revenue/cost ratio.